Prospective, monocentric observational study on the clinical use and patient satisfaction of an implantable venous access Port - Werba, Alexander; Hennes, Roland; Schuh, Fabian; Holze, Magdalena; Maichle, Barbara; Ramouz, Ali; Bauer, Mark; Braunsteffer, Kai; Knebel, Phillip; Klotz, Rosa; Pianka, Frank (Langenbeck's archives of surgery, 2025)
Long-term totally implantable venous access ports (TIVAP) are essential for administering chemotherapy and parenteral nutrition in cancer patients. This study aimed to evaluate patient satisfaction and postoperative complications, compared to existing literature, emphasizing patient-reported outcomes (PRO) as a critical factor in treatment decisions.